A comparative study on public facilities provided by local authority / Mohamed Solleh Shamsudin - Shamsudin, Mohamed Solleh (2006)
Public facilities were among the valuable assets for a country. It was very important to the public in their daily life. Without it, operations of other activity are almost incapable to be carrying out. These public facilities were provided by the government. The local authorities were responsible to provide all the facilities that the public need. In order to provide these public facilities, each local authority has their own guideline. This guideline will be use as a reference and guidance during the planning of these public facilities. Research carry out, was to identify the public facilities provided by the local authority in Selangor Darul Ehsan. It also compares the guideline for each local authority. Among other, this study is also look into satisfaction on the public facilities provided by local authorities.